Building a diverse national research advisory board - Gayle Valensky; Jeff B. Pawelek; Lauren Serpico; David Rodriguez; Maribel Pieters; Yulissa Perez; Julia Moore Vogel (Journal of Clinical and Translational Science)
In healthcare and medical research, advisory boards are now commonplace, but most boards consist of a relatively homogenous, geographically collocated group, often demonstrating demographic imbalance. It is crucial to include individuals from diverse backgrounds on community advisory boards for healthcare and medical research to address ongoing health disparities and ensure studies are more culturally competent so that we can achieve more inclusive representation. We conducted purposeful recruitment to attract a demographically diverse group of community members across the United States (U.S.) to partner with the All of Us Research Program to inform our strategies including program recruitment, engagement, retention, and incentives. Recruitment of a diverse group of advisors and purposeful community building has created a psychologically safe environment where members openly share their opinions, thoughts, and perspectives to shape various aspects of this ambitious, nationwide research program.